PERSEPSI MAHASISWA AKUNTANSI DAN HUKUM MENGENAI PENGGELAPAN PAJAK. - Payu, Anita Achmad; Marlinah, Andi (Pusat Penerbitan dan Publikasi Ilmiah FEB-UMI, 2023)
The aim is to determine the perception between accounting and law study program students regarding tax evasion. Quantitative study with the population being active students majoring in accounting and law class of 2016 who have taken taxation or tax law courses. Determining the number of samples used the Slovin formula, with a total of 96 students and using purposive sampling techniques. Hypothesis testing uses nonparametric statistical tests, namely the Mann-Whitney test. The research results show that there is no difference in ethical perceptions between accounting and law students regarding tax evasion.